Modeling the interference environment in the HF band. Issue 2 (18th February 2016) - Pederick, L. H.; Cervera, M. A.
Abstract: The performance of systems using high frequency (HF) radio waves, such as over‐the‐horizon radars (OTHR), can be strongly affected by external interferers at great distances (thousands of kilometers) from the systems receiver. However, the propagation of interference has complex behavior and is known to vary with location, time, season, sunspot number, and radio frequency. Understanding how the level of interference varies with all of these factors is important for the design of new systems such as next generation OTHR. By combining databases of known transmitters, ray‐tracing propagation, and a model ionosphere, a model of the behavior of interference at HF has been developed. Key Points: We have developed a model for external interference at HF Can model diurnal, seasonal, and geographic variations Model gives results consistent with JORN spectrum monitor data